An exploratory study of the concept of an ideal home among selected Filipino university staff - Mercado, Jeliz B.
This research explored the concept of an ideal home among selected Filipino university staff. It aimed to determine the needed and desired areas of an ideal home, its amenities, physical characteristics and psychological qualities. The research was an exploratory study which utilized survey as its primary data gathering method. Random sampling was first employed through the fishbowl method which was succeeded by non-random purposive sampling. The study had 24 qualified Filipino university staff as its respondents but only 14 of their questionnaires were considered reliable. The survey questionnaire was the foremost tool used in this study. Data gathering was conducted from January 24 to February 11, 2011. The results of the study revealed that there is a concept of an ideal home among the respondents which adhered to the practical priorities of a home. The ideal home was at least 2-storey high preferably located in the probinsya (province), which was characterized as tahimik, less stressful, relaxing and comfortable. The satisfaction of physiological needs such as hygiene, sleep, and food was the most prioritized function of an ideal home addressed by the five (5) identified needed areas of a home, the banyo, kwarto, kusina, sala and dining area. The needed and desired amenities specified by the respondents were directly associated to each area of a home. The ideal home was also perceived as a nurturing environment, this positive qualities were desired for each area. These qualities correlate with the expected attributes of an area.